Acute hepatic failure following intravenous amiodarone - Grecian, Robert; Ainslie, Mark (BMJ case reports, 2012)
A 73-year-old gentleman presented to the hospital after an episode of loss of consciousness. He had a defibrillator in situ, which on interrogation was found to have fired for an episode of ventricular fibrillation. As an inpatient he developed frequent episodes of self-terminating ventricular tachycardia, treated initially with oral amiodarone. A 24 h amiodarone infusion was started on day 3 of admission, following which the patient developed hyperventilation. Investigations revealed that this was secondary to acute hepatic and renal failure, requiring haemofiltration on the intensive care unit. Cessation of amiodarone was associated with normalisation of liver function over 48 h. The patient had normal blood and jugular venous pressures throughout days 1–4 of admission. We discuss the role of amiodarone as the predominant factor in the deterioration of this patient's liver function, versus the differential diagnosis of ischaemia-induced hepatotoxicity, citing recent research regarding this subject.